(untitled) (ADI Journal on Recent Innovation (AJRI), 2024)
This study aims to examine the relationship between Body Mass Index (BMI) and urinary incontinence in the elderly, a significant but often neglected public health concern. A cross-sectional design was used, involving elderly residents of Wisma Mulia Nursing Home. Urinary incontinence was measured using the International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF), and BMI was calculated using a standard formula. Statistical analysis with Pearson’s correlation revealed a significant association between BMI and urinary incontinence (p < 0.05), with an average ICIQ-SF score of 16.00 and a standard deviation of 10.30. These findings suggest that BMI is a contributing factor to the severity of urinary incontinence in the elderly. Clinically, the results emphasize the importance of considering BMI in the assessment and management of urinary incontinence. Interventions focusing on BMI reduction, including diet and exercise, could improve the quality of life for older adults. This aligns with the third Sustainable Development Goal (SDG), promoting good health and well-being. Future research with larger sample sizes, and exploration of factors such as physical activity and comorbidities, is essential. Longitudinal studies tracking BMI changes over time and their impact on urinary incontinence would provide deeper insights for effective interventions.